2009
DOI: 10.1007/s00249-009-0553-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and structural characterization of peripherin/RDS, a membrane protein implicated in photoreceptor outer segment morphology

Abstract: Peripherin/RDS is a member of the tetraspanin family of integral membrane proteins and plays a major role in the morphology of photoreceptor outer segments. Peripherin/RDS has a long extracellular loop (hereafter referred to as the LEL domain), which is vital for its function. Point mutations in the LEL domain often lead to impaired photoreceptor formation and function, making peripherin/RDS an important drug target. Being a eukaryotic membrane protein, acquiring sufficient peripherin/ RDS for biophysical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Wild type (WT) and p.Leu254Gln (L254Q) mutant were cloned into the pPICZ expression vector containing the c-myc epitope and the polyhistidine (His)6-tag as described before, 33 the nucleotide sequence was confirmed by Eurofins MWG using automated DNA sequencing. Pichia pastoris cells (strain KM71H) were transformed with the PmeI linearised expression vector, stably transformed cells were spread on YPD plates [1% yeast extract, 2% peptone (BD), 2% glucose, 2% agar] with media containing 100 µg/ml zeocin.…”
Section: Peripherin-2 Expression and Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild type (WT) and p.Leu254Gln (L254Q) mutant were cloned into the pPICZ expression vector containing the c-myc epitope and the polyhistidine (His)6-tag as described before, 33 the nucleotide sequence was confirmed by Eurofins MWG using automated DNA sequencing. Pichia pastoris cells (strain KM71H) were transformed with the PmeI linearised expression vector, stably transformed cells were spread on YPD plates [1% yeast extract, 2% peptone (BD), 2% glucose, 2% agar] with media containing 100 µg/ml zeocin.…”
Section: Peripherin-2 Expression and Western Blotsmentioning
confidence: 99%
“…Cells were cultured, harvested, and stored at -80°C as described before. 33 Cells were lysed upon further processing and membranes containing the WT or L254Q proteins were isolated using differential centrifugation as described previously. The membranes were dissolved in 1% n-dodecyl-β-Dmaltoside (DDM) using sequentially an 18G, 19G, and 25G needle.…”
Section: Peripherin-2 Expression and Western Blotsmentioning
confidence: 99%
“…Similarly, the percentage of α–helix in the N244K D2 loop is similar to that of the wild‐type D2 loop, but the percentage in the C214S D2 loop is reduced, even though both cause autosomal dominant retinitis pigmentosa or rod/cone dystrophy . The only other study that has examined the secondary structure of RDS reported very little change in secondary structure in the case of the P216L autosomal dominant retinitis pigmentosa mutation , although that study examined the secondary structure of the entire RDS polypeptide (not just the D2 loop), so it is difficult to compare results. These results suggest that assessing each mutation independently may be a better way to approach understanding of RDS‐associated disease, and it is likely that, for many mutations, disease arises due to a combination of molecular defects.…”
Section: Discussionmentioning
confidence: 97%
“…Their primary applications range from solubilization and stabilization of proteins to disaggregation of protein complexes and denaturation (Neugebauer 1990). In this study, the non-ionic detergents, Triton X-100 and DDM, were employed to isolate PS-I from spinach thylakoid in aqueous solution, which have been used extensively in studies of photosynthetic membranes (Ge et al 2010;Iwuchukwu et al 2010;Tsiotis et al 1993;Vos et al 2010). …”
Section: Effect Of Detergent Concentration On Ps-i Activitymentioning
confidence: 99%